2015
DOI: 10.3390/rs8010022
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Fractional Cropland Distribution in Mato Grosso, Brazil Using Time Series MODIS Enhanced Vegetation Index and Landsat Thematic Mapper Data

Abstract: Mapping cropland distribution over large areas has attracted great attention in recent years, however, traditional pixel-based classification approaches produce high uncertainty in cropland area statistics. This study proposes a new approach to map fractional cropland distribution in Mato Grosso, Brazil using time series MODIS enhanced vegetation index (EVI) and Landsat Thematic Mapper (TM) data. The major steps include: (1) remove noise and clouds/shadows contamination using the Savizky-Gloay filter and tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The identification of irrigation pixels is consistent with actual irrigation samples in field surveys and statistical areas ( Table 3). It is possible to supervise the distribution and the area of irrigation automatically using satellite-based datasets, avoiding visual interpretation [55][56][57] of high-resolution images [58] and much fieldwork, as well as substantially improving the method's repeatability and applicability.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of irrigation pixels is consistent with actual irrigation samples in field surveys and statistical areas ( Table 3). It is possible to supervise the distribution and the area of irrigation automatically using satellite-based datasets, avoiding visual interpretation [55][56][57] of high-resolution images [58] and much fieldwork, as well as substantially improving the method's repeatability and applicability.…”
Section: Discussionmentioning
confidence: 99%
“…The key identification stage selection is fundamental for constructing a seasonal dynamic index, which is critical for cropland mapping in the Brazilian Amazon region. As almost all images are contaminated by clouds in the rainy season, a feasible means is to use slices of discrete time series data instead of entire continuous time series data for a year for crop mapping [26] . As the EVI profiles in cropland area vary regularly at different stages (e.g., the sowing, growing, and harvest stage), three key identification stages: the sowing (Stage 1, DOY:225-289), growing (Stage 2, DOY:305-001), and harvest (Stage 3, DOY:017-081) seasons are the key identification stages for cropland mapping [26] .…”
Section: Key Identification Stage and Seasonal Dynamic Indexmentioning
confidence: 99%
“…The seasonal dynamic index (SDI) model was proposed by Zhu et al. The model can be elaborated by Equations (2)-(8) [26] : (8) where, SDI represents the seasonal dynamic index; and SDI 1 and SDI 2 correspond to the seasonal dynamic index at different stages; EVI d , EVI g , and EVI h are cloud-free EVI composites from the dry to wet season transition, the growth, and the harvest season, respectively; EVI 225 , EVI 241 , …, EVI 353 , are the multi-temporal MODIS EVI products, and the number subscript is the acquired day of the year (DOY); Slp mask is the topographic factor mask where the slope is derived from STRM data; Slp mask is a slope mask;…”
Section: Key Identification Stage and Seasonal Dynamic Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the Moderate-Resolution Imaging Spectroradiometer (MODIS) sensor on board the Terra satellite provides an adequate imaging configuration for crop monitoring based on (1) an almost-daily revisit time; (2) a moderate spatial resolution of 250-m, considered adequate for mapping large-scale agricultural fields (Lobell and Asner 2004); and (3) a geometric quality that is high enough for time series analysis (Justice et al 2002). A study conducted by Lobell and Asner (2004) concluded that MODIS images have considerable advantages in the characterization of extensive agricultural crops, mainly due to their higher temporal resolution, and many studies focused on Brazil have highlighted the efficiency of the MODIS time series of vegetation indices for mapping cropland, crop expansion Macedo et al 2006;Gusso et al 2014, Zhu et al 2016 and cropping system management (Galford et al 2008;Arvor et al 2012;Brown et al 2013).…”
Section: Introductionmentioning
confidence: 99%